The impact of immigration on the Australian economy - Fell, G (1991)
Australian immigration policy has traditionally been justified as a means to ensure national security and promote economic development. Neither of these rationales retains much contemporary force. A larger population is no longer regarded as critical to Australia's defensive capacity, and the quest for economic development, synonymous with aggregate growth, has been superseded by a concern about per capita growth performance. While humanitarian and cultural justifications for immigration have been advanced, they are either restricted in scope or contentious. Currently, the programme is operating on a large scale without a clear rationale. The purpose of this work is to investigate the economic consequences of immigration, and so consider whether the economic rationale may be recast in an alternative form. In this chapter, the existing literature is reviewed and a strategy for carrying the analysis further is outlined.